2001
DOI: 10.1136/ip.7.suppl_1.i59
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Disability Awareness and Risk Education (AgDARE) for high school students

Abstract: Objective-Develop and test a farm health and injury prevention educational intervention for high school agriculture students. Setting-Twenty one high schools in Kentucky, Iowa, and Mississippi. Methods-A quasiexperimental crossover design was used to test the eVectiveness of two sets of instructional materials designed through participatory action research with agriculture teachers and students. Narrative simulations based on farm work stories and simulations of farm work while students pretended to have a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 17 publications
1
40
0
Order By: Relevance
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The studies varied widely in the interventions and outcomes studied, the types of injury targeted by the interventions, and the study design and methodologic rigor (QI range: [11][12][13][14][15][16][17][18][19][20]. Although all studies evaluated educational interventions, their focuses varied; 7 were designed for, or examined in, the school setting, [29][30][31][32][33][34][35] 12 were community-based, [36][37][38][39][40][41][42][43][44][45][46][47] and 1 was designed for use on the farm. …”
Section: Effectiveness Of Other Interventions To Prevent Childhood Agmentioning
confidence: 99%
See 4 more Smart Citations
“…[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The studies varied widely in the interventions and outcomes studied, the types of injury targeted by the interventions, and the study design and methodologic rigor (QI range: [11][12][13][14][15][16][17][18][19][20]. Although all studies evaluated educational interventions, their focuses varied; 7 were designed for, or examined in, the school setting, [29][30][31][32][33][34][35] 12 were community-based, [36][37][38][39][40][41][42][43][44][45][46][47] and 1 was designed for use on the farm. …”
Section: Effectiveness Of Other Interventions To Prevent Childhood Agmentioning
confidence: 99%
“…29,30,34,38,40,44,47 Ten studies measured changes in safety attitudes and/or behavior as 1 of their principal outcomes. 29,35,39,40,[42][43][44][45]47,48 Many of these studies evaluated short-term changes; 2 studies reported outcomes measured the year after training, 42,43 and 1 study evaluated effects on behavior at 1 year after the intervention for a small subset of the original sample. 35 One study measured recall of farm hazards at 1, 14, and 28 days and the extent to which children made comparisons with their own farms.…”
Section: Effectiveness Of Other Interventions To Prevent Childhood Agmentioning
confidence: 99%
See 3 more Smart Citations